DNA Engineering and Hepatitis B Virus Replication - Gan, Chun-yang; Cui, Jing; Zhang, Wen-lu; Wang, Yu-wei; Huang, Ai-long; Hu, Jie-li (Frontiers in Microbiology, 2021)
Recombinant DNA technology is a vital method in human hepatitis B virus (HBV), producing reporter viruses or vectors for gene-transferring. Researchers have engineered several genes into the HBV genome for different purposes; however, a systematical analysis of recombinant strategy is lacking. Here, employing a 500-bp deletion strategy, we scanned the HBV genome and identified 2 regions, the region I (from nt 2118 to 2814) and region II (from nt 99 to 1198), suitable for engineering. Ten exogenous genes, including puromycin N-acetyl transferase gene (Pac), blasticidin S deaminase gene (BSD), Neomycin-resistance gene (Neo), Gaussia luciferase (Gluc), Nanoluc (Nluc), copGFP, mCherry, UnaG, eGFP, and tTA1, were inserted into these 2 regions and fused into the open reading frames (ORFs) of hepatitis B core protein (HBC) and hepatitis B surface protein (HBS) via T2A peptide. Recombination of 9 of the 10 genes at region 99-1198 and 5 of the 10 genes at region 2118-2814 supported the formation of relaxed circular (RC) DNA. HBV DNA and HBV RNA assays implied that exogenous genes potentially abrogate RC DNA by inducing the formation of adverse secondary structures. This hypothesis was supported because sequence optimization of the UnaG gene based on HBC sequence rescued RC DNA formation. Findings from this study provide an informative basis and a valuable method for further constructing and optimizing recombinant HBV and imply that DNA sequence might be intrinsically a potential source of selective pressure in the evolution of HBV.